Application of the formal procedure defined to evaluate, monitor and improve the process of collaborative learning in its process stage through the creation of mechanisms - Agredo Delgado, Vanessa; Alberto Collazos, Cesar; Paderewski Rodríguez, Patricia (I+ T+ C- Research, Technology and Science, 2016)
With the constant development of information and communication technologies, new learning opportunities have been opened up, and the potential of new technologies and the ways in which they can be exploited have been recognized. Therefore, the use of digital technology has been increased to support teaching and learning. In these cases, the technology has also been a great boom to support collaborative learning, which is why this article shows how to apply the formal procedure generated to evaluate, monitor and improve the collaborative learning process, taking into account the execution of two case studies that were developed in different educational environments. The results indicated that it is not enough to provide a group of people with some activity and a software tool; it is also necessary to analyze all the external factors that can influence this process, mainly: characteristics of the groups, activities and technology. In addition to involving the use of a tool that contains the necessary mechanisms that allow the teacher to carry out monitoring and evaluation of the collaborative process, thus generating the improvement of this.